PRESCRIPTION PATTERN AND THERAPEUTIC RESPONSE OF VARIOUS ANTI HYPERTENSIVE DRUGS FOR THE HYPERTENSIVE PATIENTS AT PRIVATE HOSPITALS IN TAMILNADU, INDIA (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present study was conducted in order to establish the therapeutic responses and prescription pattern of various antihypertensive agents in patients with mild, moderate and severe hypertension. Prospective and comparative study was carried out on 500 patients attending the cardiology out patients department at private hospitals in Tamilnadu, India. Patients of either sex aged between 18-60 years suffering from hypertension and to evaluate the characterization, drug therapy (mono or combination) of five major categories of antihypertensive drugs in patients with hypertension. Out of 500 patients, males (49.29 ± 6.5) and females (50.63 ± 6.5) participated in the study. This study revealed that most of the patients were on mono therapy (43%, Male and 28% Female) and in combination therapy (17% male and 12% Female). In mono therapy, five classes of drugs were used. These were diuretics (33%), beta-blockers (20%), calcium channel blockers (19%), ACE inhibitors (17%) and angiotensin II receptor blocker (11%). Among mono therapy of drugs, diuretics were prescribed most whereas angiotensin II receptor blocker were least used, In combination therapy, angiotensin II receptor blocker and thiazide diuretic was given to the majority of the patients (42%), beta blocker and thiazide diuretic were (32%), calcium channel blocker and beta blocker were (15%) and ACE Inhibitor and calcium channel blocker were (10%). The present study represents the current prescribing pattern of anti-hypertensive drugs and it highlights certain shortcomings in the existing prescribing practice. There is a considerable scope for improvement on patient’s interaction with pharmacist and doctors and needs to improve pharmaceutical care on disease and drug knowledge for the effective blood pressure control.